An Exploration of the Criminal Thinking Processes in Criminal Offenders - Lemieux, Mark V (2020)
This study sought to learn about Criminal Thinking patterns of thought in former criminal offenders. The discovery of this information is important to several fields in the formulation of treatment programs toward the elimination of criminal behavior. This research is based on the theory formulated by Yochelson and Samenow, and expanded on by Walters, that holds that Criminal Thinking patterns develop along a continuum and can lead to criminal behavior in some. Specifically, this study sought to learn whether criminal offenders were aware of their Criminal Thinking patterns and if that awareness impacted their criminal behavior. This qualitative phenomenological study relied on semi-structured interviews of 6 former criminal offenders who had served a sentence in a Federal Correctional facility, and the thematic analysis of the transcripts of those interviews to draw conclusions. The results indicate that several themes emerged: (a) awareness of criminal behavior, (b) purposefulness in the commission of crimes (c) increase in frequency and complexity of criminal behavior (d) lack of concern for others (victims, family, friends); (e) awareness of inevitable detection and negative outcome, (f) realization of impact of criminal behavior and remorsefulness. The findings of this study conclude that criminals do have an awareness of their criminal thinking patterns before during and after the commission of criminal acts and that and that they are affected by that awareness in how they act. The results of this study may lead to positive social change in reducing or eliminating criminal behavior in former criminal offenders and others